The Mediating Role of Online Tracking in the Relationship Between Delivery Timeliness and Customer Satisfaction in E-Commerce - Sirait, David Pandapotan; Sitorus, Marthaleina Ruminda; Lermatan, Esterlinus Edwin; Pratiwi, Sekar Widyastuti; Parlindungan, Purbanuara (Dinasti International Journal of Management Science, 2026)
This study aims to analyze the determinants of customer satisfaction in the e-commerce landscape by examining the roles of timeliness of delivery and online tracking. In a competitive market, customer satisfaction has become a crucial indicator of success, where logistics and supply chain management play a central role. This research proposes and tests a mediation model where online tracking is hypothesized to mediate the relationship between timeliness of delivery and customer satisfaction for Shopee Indonesia users. Using a quantitative approach, data were collected through a survey of 150 Shopee consumers in Indonesia and analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results confirm that all four proposed hypotheses were accepted. The findings indicate a significant positive influence of timeliness of delivery on both online tracking and customer satisfaction. Online tracking also has a strong positive effect on customer satisfaction. Crucially, the study validates that online tracking acts as a significant mediator in the relationship between timeliness of delivery and customer satisfaction. These findings imply that e-commerce platforms must prioritize both the reliability of delivery and the transparency of the tracking process to enhance overall customer satisfaction.